Sosialisasi kewirausahaan dan inovasi briket arang pada masyarakat Desa Pondokagung - Anggraeni, Vira Ayu (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the use of corn cob waste to make it a productive business. Pondokagung Village has great potential for development because of its productive population and ample natural resources, especially in the agricultural sector. This research uses an observation method that begins with the large piles of corn waste that have stalled in Pondokagung Village, one of the villages in Kasembon District, Malang Regency, East Java Province. So, through literature research carried out by the 105 KKM UIN Malang group, a charcoal product from corn cobs was obtained which can be used to overcome the problem of corn waste. This research is important to do to improve the economy of Pondokagung Village. Therefore, participants in this entrepreneurship socialization were prioritized among village officials and several community representatives from each hamlet so that they could follow up on the results of the socialization activities because of the many benefits and advantages produced from corn charcoal briquettes.